Faktor-faktor pengunduran diri karyawan pada Bank Syariah Indonesia area Riau: Pendekatan fenomenologi - Merry Meilany; Mohd. Winario (STAI Auliaurrasyidin Tembilahan, 2026)
The purpose of this study is to explore in depth the reasons behind employees' The purpose of this study is to explore in depth the reasons behind employees' resignation decisions from Islamic banks, particularly at Bank Syariah Indonesia in the Pekanbaru City area of ​​Riau. The research method used a qualitative phenomenological approach. Data were obtained through in-depth interviews with former employees who resigned voluntarily. The data analysis technique used an interpretive phenomenological analysis (IPA) approach. The results show that resignation decisions are influenced by various factors, such as work pressure, authoritative leadership, limited career development opportunities, and a mismatch between organizational culture and Islamic values. Employees feel disappointed when the principles of justice, trustworthiness, and transparency are not reflected in work practices. In addition, conflicts between personal values ​​and the search for a more spiritual meaning in life also contribute to resignation decisions. In conclusion, non-technical factors such as value mismatches are the main reasons for resignation, not solely workload or career path.